Hadith #3931 - Sunan Abi Dawud - Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id bin Jmhan سعيد بن جمهان; Safinah (Sunan Abi Dawud)
Juwayriyyah, daughter of al-Harith ibn al-Mustaliq, fell to the lot of Thabit ibn Qays ibn Shammas, or to her cousin. She entered into an agreement to purchase her freedom. She was a very beautiful woman, most attractive to the eye. Aisha said: She then came to the Messenger of Allah (ﷺ) asking him for the purchase of her freedom. When she was standing at the door, I looked at her with disapproval. I realised that the Messenger of Allah (ﷺ) would look at her in the same way that I had looked
Grade: Hasan

Hadith #4644 - Sunan Abi Dawud - Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Sa'id bin Jmhan سعيد بن جمهان; Safinah (Sunan Abi Dawud)
These clients (i.e., non-Arabs) are to be struck and cut off. I swear by Allah, if I strike a stick with a stick, I would annihilate them like the day that passed away. Al-hamra means clients or non-Arabs.
Grade: Sahih

Hadith #4645 - Sunan Abi Dawud - al-'Awwam bin Hushab العوام بن حوشب بن يزيد; Amr bin 'Awn/'Auf bin Aws; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Sa'id bin Jmhan سعيد بن جمهان; Safinah (Sunan Abi Dawud)
I prayed the Friday prayer with al-Hajjaj and he addressed. He then transmitted the tradition of Abu Bakr b. ‘Ayyash. He said in it: Hear and obey the caliph of Allah and his select ‘Abd al-Malik bin Marwan. He then transmitted the rest of the tradition, and said: If I seized Rabi’ah for Mudar. But he did not mention the story of the clients (i.e. non Arabs).
Grade: Sahih